From Sinai to Jerusalem: Shema Yisrael and the Outpouring of the Holy Spirit in a Pentecostal Perspective - Henky Johansja (QUAERENS: Journal of Theology and Christianity Studies, 2024)
This article explores the theological trajectory from Shema Yisrael—the foundational confession of Israel’s monotheism—to the outpouring of the Holy Spirit in Jerusalem as interpreted within the Pentecostal tradition. The background lies in the tension between Israel’s strict declaration of God’s oneness (יְהוָה אֶחָד) at Sinai and the Pentecostal experience of the Spirit (πνεῦμα ἅγιον) that shaped the global church. The purpose of this study is to demonstrate that Israel’s monotheism is not rejected but fulfilled in the Pentecostal encounter, where Shema is reinterpreted through Christ and the Spirit into a relational and living confession. Methodologically, the research employs a qualitative theological approach using biblical analysis, patristic interpretations, and contemporary Pentecostal pneumatology to examine Shema in its historical, liturgical, and theological dimensions. The findings reveal that Pentecostal theology sees a continuity: Sinai’s written law transforms into the Spirit’s living law, affirming the Shema in a Christocentric and pneumatological way. The contribution of this study is to show that Pentecostal faith and practice offer a unique perspective in bridging Jewish monotheism and Christian Trinitarianism, presenting Shema as the foundation for global mission, transformative spirituality, and ecclesial identity empowered by the Holy Spirit.